Assessment of particulate matter in a university campus during spring season - Behera S.K.; Mudgal A. (My University, 2025)
We aim to study particulate matter (PM) exposure at university campuses. The campus of Banaras Hindu University in the city of Varanasi was taken as a case study. PM concentrations were recorded using a portable aerosol monitor during peak hours for 45 days (Febru-ary–March 2021) at several intersections inside the campus. PM exposure was substantially higher during the weekdays than on weekends. Due to higher humidity conditions, PM2.5 (fine particles) exposure was higher during February than during March. March witnessed an increased PM10 (coarse particles) exposure because of higher atmospheric temperature, which caused greater resuspension of the coarse particles. PM concentration inside the campus was affected by traffic volume, the number of intersections, and the presence of speed brea-kers. PM2.5 (54 μg m–3) was lower than the limits set by the National Ambient Air Quality Standards in India (60 μg m–3). In contrast, PM10 (115 μg m–3) exceeded the standard limits (100 μg m–3). Both PM2.5 and PM10 surpassed the daily limit (PM2.5: 15 μg m–3 and PM10: 45 μg m–3) set by the World Health Organization (WHO). Fine particulate matter (PM2.5) is more haz-ardous to health than coarse particulate matter (PM10). Consequently, the air quality on the campus was mode-rate as per the national norms. © 2023, Current Science. All Rights Reserved.